CAUSES OF THE RECENT TEACHERS STRIKES IN KENYA - Mugho, Steven Mwakisha (Journal of Public Policy and Administration, 2017)
Purpose: To establish the causes of the participation in the current teachers strike in Kenya. Methodology: The study utilized a descriptive research design. Findings: Results indicated that an increase in the unit change of poor remuneration would result to an increase in participation of teachers in the teachers strike by 0.379 units. Results also revealed that an increase in the unit change of lack of implementation of the collective bargaining agreement would result to an increase in participation of teachers in the teachers strike by 0.403 units. Results also showed that an increase in the unit change of delayed job group promotion would result to an increase in participation of teachers in the teachers strike by 0.108 units. Further, results revealed that an increase in the unit change in poor working conditions would result to an increase in participation of teachers in the teachers strike by 0.488 units. Unique contribution to theory, practice and policy: The results of this study will be significant to the ministry of education, this study will contribute valuable information on the causes of the current teachers strike. Thus, the various stakeholders in the ministry will make decisions from an informed position of what is happening on the ground. The study findings may assist the Teachers Service Commission; as the teacher's employer in ensuring that teachers are given better working environments. The findings on the causes of the current teachers strike may help the Government to provide for the needs of its employees. The study will be used by the Government to understand the justification of the strikes and the possible remedies thereof. The study may also give more insight to KNUT officials on the causes of the current teachers' strike which would give them better direction as they advocate for their grievances. It will also provide an in depth justification of the effectiveness of dialogue and engagement, in the provision of teaching services. The study may also provide useful data to future researchers in the field of teacher's trade unions in Kenya and teachers performance.